2011
DOI: 10.1111/j.1654-1103.2010.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Sampling procedures and species estimation: testing the effectiveness of herbarium data against vegetation sampling in an oceanic island

Abstract: Questions: What is the relationship between species assemblages in herbarium collections and species abundances in the field, and how trustworthy are herbarium data in vegetation science? Location: Guadalupe Island, Baja California, Mexico. Methods: We compared species‐abundance distribution and evenness in 110 vegetation plots in Guadalupe Island against data from four herbaria. We tested whether the relative frequencies derived from herbarium specimens differed significantly from species frequencies in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…Its sampling variance (VAR QX ) is approximated as (SD2(n)X2(n) )2+ (SD1(n)X1(n) )2. As in the absence of singletons, the assemblage is considered to be well sampled, and SD of X will be zero (Colwell et al . ), to account for any under‐ or overestimation of singletons and doubletons (collectors may put more effort on registering the rarest species, Garcillan & Ezcurra , or try to obtain two specimens to capture morphological diversity of the species, e.g. males and females; flowering and fruiting plant specimens), we a priori excluded cells with very poor quality of sampling and we used bootstrapping to calculate SD of X (by re‐sampling the data we create a corrected estimator of the number of unseen species, where the effect of under/oversampling of singletons is reduced).…”
Section: Methodsmentioning
confidence: 99%
“…Its sampling variance (VAR QX ) is approximated as (SD2(n)X2(n) )2+ (SD1(n)X1(n) )2. As in the absence of singletons, the assemblage is considered to be well sampled, and SD of X will be zero (Colwell et al . ), to account for any under‐ or overestimation of singletons and doubletons (collectors may put more effort on registering the rarest species, Garcillan & Ezcurra , or try to obtain two specimens to capture morphological diversity of the species, e.g. males and females; flowering and fruiting plant specimens), we a priori excluded cells with very poor quality of sampling and we used bootstrapping to calculate SD of X (by re‐sampling the data we create a corrected estimator of the number of unseen species, where the effect of under/oversampling of singletons is reduced).…”
Section: Methodsmentioning
confidence: 99%
“…Despite their diversity, widespread appeal, and conservation status (Brundrett, ; Swarts & Dixon, ), orchids are less collected than the other similarly diverse plant families in Australian herbarium records. Species rarity can hinder collection, but in general, museum collections tend to overrepresent rare species (Garcillán & Ezcurra, ; Guralnick & Van Cleve, ). As yet, there are no other studies of whether herbarium collections and collecting effort represent the natural diversity and abundance of orchids.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of relationships (Ra 2 value) of the models that included the area of the native range, the residence time and the plant hardiness as explanatory variables is high, despite the fact that all the information sources we used (plant atlases, herbarium specimens) suffer from biases. Biases are especially of concern for herbarium specimens, which are not necessarily sampled in proportion with the size of the plant population in the field (Garcillán et al ., ; Garcillán & Ezcurra, ), nor with a constant collecting effort over time (Prather et al ., ; Rich, ; Hofmann et al ., ; Lavoie et al ., ). Plant atlases also have several spatial and temporal sampling biases (Robertson et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…To what extent the number of herbarium specimens in Québec is an indicator of population size or of the area occupied by a species remains to be substantiated; it is likely a combination of both. Several studies have shown that the number of herbarium specimens is a good indicator of the size of a plant population in the field (MacDougall et al, 1998;Vetaas, 2000;Puyravaud et al, 2003;Wu et al, 2005;Phillips et al, 2011), although common species and rare species are usually under-or over-represented in herbaria, respectively (Garcillán et al, 2008;Garcillán & Ezcurra, 2011). The collections of MT and QFA are not computerized, so the number of specimens for each species was manually counted (total: 35,574 specimens).…”
Section: Number Of Occurrences In the Introduced Rangementioning
confidence: 99%